2012
DOI: 10.1111/j.1582-4934.2011.01371.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of myosin RLC phosphorylation in normal and cardiomyopathic mouse hearts

Abstract: Phosphorylation of the myosin regulatory light chain (RLC) by Ca2+-calmodulin–activated myosin light chain kinase (MLCK) is known to be essential for the inotropic function of the heart. In this study, we have examined the effects of MLCK-phosphorylation of transgenic (Tg) mouse cardiac muscle preparations expressing the D166V (aspartic acid to valine)–RLC mutation, identified to cause familial hypertrophic cardiomyopathy with malignant outcomes. Our previous work with Tg-D166V mice demonstrated a large increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
64
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 43 publications
8
64
0
Order By: Relevance
“…To follow up on our in vitro experiments (6,17) and to test the hypothesis that pseudo-RLC phosphorylation is capable of preventing the development of detrimental D166V phenotypes in vivo, we produced three lines of the α-MHC-driven transgenic "rescue mice" expressing a constitutively phosphorylated RLC-S15D (serine mutated to aspartic acid) in a background of RLC-D166V. Transgene expression and the incorporation of the S15D-D166V mutant into the mouse myocardium were determined in ventricular and atrial lysates (four to six hearts per group) or in myofibrils purified from three to seven hearts per line (L1, L3, and L5).…”
Section: Resultsmentioning
confidence: 99%
“…To follow up on our in vitro experiments (6,17) and to test the hypothesis that pseudo-RLC phosphorylation is capable of preventing the development of detrimental D166V phenotypes in vivo, we produced three lines of the α-MHC-driven transgenic "rescue mice" expressing a constitutively phosphorylated RLC-S15D (serine mutated to aspartic acid) in a background of RLC-D166V. Transgene expression and the incorporation of the S15D-D166V mutant into the mouse myocardium were determined in ventricular and atrial lysates (four to six hearts per group) or in myofibrils purified from three to seven hearts per line (L1, L3, and L5).…”
Section: Resultsmentioning
confidence: 99%
“…38). The measurement of diameter was taken at approximately three points along the muscle strip length with an SZ6045 Olympus microscope (zoom ratio of 6.3:1, up to 189 ϫ maximum magnification) and averaged (38). For the measurement of passive tension (in pCa 8 solution) in response to muscle stretch, the muscle strip was first released and stretched until it began generating tension (53).…”
Section: Steady-state Force Measurements In Transgenic Mouse Papillarmentioning
confidence: 99%
“…Maximal steadystate tension measured in pCa 4 solution was expressed in newtons per cross section of the muscle strip (N/m 2 ; Ref. 38). The measurement of diameter was taken at approximately three points along the muscle strip length with an SZ6045 Olympus microscope (zoom ratio of 6.3:1, up to 189 ϫ maximum magnification) and averaged (38).…”
Section: Steady-state Force Measurements In Transgenic Mouse Papillarmentioning
confidence: 99%
“…DCMlinked D94A-RLC mutation was shown to significantly alter the N-terminal α-helical region of the RLC, and trigger intramolecular rearrangements in the RLC molecule that ultimately resulted in alterations of RLC function . Other studies from Szczesna et al's laboratory have also revealed compromised RLC phosphorylation in several different HCM models (Tg-R58Q and Tg-D166V), occurring concurrently with diminished maximal tension and altered Ca 2+ sensitivity of contraction (Abraham et al 2009;Kerrick et al 2009a;Muthu et al 2012b). Studies with HCM causing mutations in the myosin RLC suggest a correlation between the severity of cardiomyopathy phenotype and the level of RLC phosphorylation in vivo (Huang et al 2014;Kerrick et al 2009b;Muthu et al 2012b).…”
Section: Genetic Mutations In Myosin Regulatory Light Chain Lead To Cmentioning
confidence: 95%
“…Other studies from Szczesna et al's laboratory have also revealed compromised RLC phosphorylation in several different HCM models (Tg-R58Q and Tg-D166V), occurring concurrently with diminished maximal tension and altered Ca 2+ sensitivity of contraction (Abraham et al 2009;Kerrick et al 2009a;Muthu et al 2012b). Studies with HCM causing mutations in the myosin RLC suggest a correlation between the severity of cardiomyopathy phenotype and the level of RLC phosphorylation in vivo (Huang et al 2014;Kerrick et al 2009b;Muthu et al 2012b). The compromised phosphorylation of RLC mutants compared to WT suggests that diminished RLC phosphorylation observed in HCM hearts may have an important physiological role and is central to the understanding of the mutation-elicited detrimental cardiomyopathy phenotype.…”
Section: Genetic Mutations In Myosin Regulatory Light Chain Lead To Cmentioning
confidence: 95%